Meri dost - Naheed, Hasan (book group Karachi, 1994)
"Meri Dost" is likely a title of a children's book in Urdu, which translates to "My Friend." The book could be about friendship, sharing, kindness, or any other theme related to friendship. It might feature characters like a child and their pet, two friends playing together, or a child making a new friend.